Conceptual Clothing : exhibition devised by Fran Cottell and Marian Schoettle. - Ikon Gallery, Birmingham; Harris Museum & Art Gallery, Preston; Peterborough City Museum & Art Gallery, Peterborough; Spacex Gallery, Exeter; Stoke on Trent City Museum & Art Gallery (Birmingham : Ikon Gallery, 1986)
Araeen, Rasheed ; Bailey, Bridget ; Broadhead, Caroline ; Brooker, Sarah ; Camp, Sokari Douglas ; Cottell, Fran ; Cuddihy, Mikey ; Freeman, Susie ; Garrard, Rose ; Hatoum, Mona ; Heron, Susanna ; Hiller, Susan ; Holmes, Cas ; Johnson, Steve ; Kelly, Mary ; Layzell, Richard ; Schoettle, Marian ; Sebastiane ; Snaith, Yolande ; Thomas, Deb ; Ward, David ; Wiggins, Jenny ; Williams, Lois
Conceptual Clothing, Ikon Gallery, Birmingham, 6 December 1986 - 4 January 1987 / Harris Museum & Art Gallery, Preston, 14 February - 21 March 1987 / Peterborough City Museum & Art Gallery, Peterborough, 4 April - 2 May 1987 / Spacex Gallery, Exeter, 16 May - 13 June 1987 / Stoke on Trent City Museum & Art Gallery, 27 June - 29 July 1987 / etc.
boek